The impact of digital techologies on the tranformation of the labor market and recruitment - Оleg Havryliuk; Taras Bozhydarnik (Економічний форум)
The article reveals the impact of introducing new innovative information technologies on thetransformation of the labour market itself and the methods/tools for ensuring its functioning. The latest trends in the dynamics of the labour market and recruiting are identified, in particular, robotics using artificial intelligence, industry transformation, the spread of remote work and the need to practice empathy taking into account the age mentality of generations. It is shown that the digital transformation of recruiting has accumulated a large number of digital tools, the position is argued, according to which the use of archaic methods (paper media, face-to-face interview) has become impossible in online conditions. It is proven that the key to effective digitization of recruiting is the use of the latest technologies such as artificial intelligence (AI), augmented reality (AR), virtual reality (VR), etc. The impact of millennials, and especially Generation Z, on the transformation and disappearance of industries significant for the previous generation, has been clarified. The thesis argues that employers need to be aware of gendered manifestations of empathy and adapt approaches accordingly to minimize the risk of losing the best talents seeking to embrace workplaces that correspond to their values. Attention is focused on the fact that taking into account the mentality of the new generation ‒ generation Z, ‒ which is already actively influencing the modification of strategies of high-tech companies, development trends in the sphere of leisure and other important spheres of life, is particularly relevant. The main priorities of Generation Z have been specified: travel, communication, new discoveries and emotions, free movement between countries, performing tasks from anywhere in the world, and areas of activity with the possibility of choosing the length of the working day and location. The study’s results can be considered when developing a strategy for the post-war development of Ukraine. It was emphasized that their key competence is finding and skillfully using the necessary information